α-Chitinase activity among lactic acid bacteria - Leisner, Jørgen J.; Vogensen, Finn K.; Kollmann, Johannes; Aideh, Bashir; Vandamme, Peter; Vancanneyt, Marc; Ingmer, Hanne (Systematic and applied microbiology, 2008)
Chitin is a polysaccharide widely distributed in nature. Among 115 strains from 29 species of lactic acid bacteria only strains belonging to Carnobacterium divergens and Carnobacterium maltaromaticum hydrolyzed α-chitin. This activity was not affected by temperature (10 °C versus 30 °C) and in most cases not subject to glucose catabolite repression.